2022
DOI: 10.1242/dmm.049707
|View full text |Cite
|
Sign up to set email alerts
|

An adherent-invasive Escherichia coli-colonized mouse model to evaluate microbiota-targeting strategies in Crohn's disease

Abstract: Adherent-Invasive Escherichia coli (AIEC) was investigated for its involvement in the induction/chronicity of intestinal inflammation in Crohn's disease (CD). AIEC gut establishment is favoured by overexpression of the glycoprotein CEACAM6 in the ileal epithelium. We generated a transgenic mouse model named ‘Vill-hCC6’, in which the human CEACAM6 gene was under the control of the villin promoter, conditioning expression in the small intestine. We demonstrated that CEACAM6 is strongly expressed in the small int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…These two genes have been previously characterized in vivo and in vitro , and thus we reasoned that characterizing their phenotypes would allow us to benchmark our model against published in vivo and in vitro AIEC models. Prior studies show that the burden of AIEC LF82Δ fimH is significantly decreased at 2 and 10 dpi in two different mouse models that express mammalian CEACAM6 in the intestine (8, 57). Deletion of ibeA did not impact the burden of AIEC strain NRG857c in mice, although it did contribute to invasion and intracellular survival in vitro (20).…”
Section: Discussionmentioning
confidence: 99%
“…These two genes have been previously characterized in vivo and in vitro , and thus we reasoned that characterizing their phenotypes would allow us to benchmark our model against published in vivo and in vitro AIEC models. Prior studies show that the burden of AIEC LF82Δ fimH is significantly decreased at 2 and 10 dpi in two different mouse models that express mammalian CEACAM6 in the intestine (8, 57). Deletion of ibeA did not impact the burden of AIEC strain NRG857c in mice, although it did contribute to invasion and intracellular survival in vitro (20).…”
Section: Discussionmentioning
confidence: 99%
“…Both fimH and ibeA have been extensively characterized in vivo and in vitro , and thus we used them to benchmark our model against published in vivo and in vitro AIEC models. Deletion of fimH significantly decreased LF82 colonization in two different mouse models that express mammalian CEACAM6 in the intestine ( 8 , 56 ). Deletion of ibeA did not impact the burden of AIEC strain NRG857c in mice, although it did contribute to invasion and intracellular survival in vitro ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phage therapy is a biological treatment against bacterial infection; however, it targets only a limited number of bacterial strains. An interesting study showed that LF82-P2, LF82-P6, and LF82-P8 phages were effective against AIEC in a mouse model [67]. Galtier et al [68] found that a single day of oral treatment with bacteriophages significantly decreased intestinal colonization by AIEC strain LF82.…”
Section: -Phage Therapymentioning
confidence: 99%